Randomized controlled trial on the efficacy of forest walking compared to urban walking in enhancing mucosal immunity - Hiroko Ochiai; Shigeru Inoue; Gaku Masuda; Shiho Amagasa; Tomohiko Sugishita; Toshiya Ochiai; Naoko Yanagisawa; Yoshio Nakata; Michiko Imai (Scientific Reports)
Abstract Scientific research on forest therapy’s preventive medical and mental health effects has advanced, but the need for clear evidence for practical applications remains. We conducted an unblinded randomized controlled trial involving healthy men aged 40–70 to compare the physiological and psychological effects of forest and urban walking. Eighty-four participants were randomly assigned to either the forest or urban group, with 78 completing 90-min walks and analysis. The primary outcome measured was the change in saliva-secreted immunoglobulin A (sIgA) levels. Evaluating researchers were blinded to the groups, but participants and on-site staff were not. Here, we demonstrate a significant increase in saliva-secreted immunoglobulin A (sIgA) levels in the forest group. Furthermore, forest walking resulted in improved mood, including a reduction in stress hormone levels. In conclusion, mindful forest walking has the potential to enhance immunity and promote health. Clinical trial registration: University Hospital Medical Information Network. Trail registration number: UMIN000045851. Approval date: 25/10/2021.